Qualitative measures of family functions affecting child deprivation - Karapetyan, Tatevik (ՀՀ ԳԱԱ)
The article discusses the phenomenon of child deprivation from parental care, with the aim of extracting the basic measurements of family functions that are significant in terms of child abandonment. Specifically, the approaches proposed by Bowlby, Spence, Kadushin and Burnstein were discussed in the context of risk factors causing child abandonment. Besides, the concept of family resilience was studied as a new perspective on family functioning. Հոդվածը քննարկում է երեխաների խնամազրկության երևույթը՝ նպատակ ունենալով դուրս բերել ընտանիքի գործառնման այն հիմնական չափումները, որոնք նշանակալի են երեխաների լքման տեսանկյունից։ Այս համատեքստում հոդվածում անդրադարձ է կատարվում Սպենսի, Բոուլբիի, Կադուշինի և Բարնշտեյնի՝ ընտանիքում մանկալքության տեսանկյունից ռիսկային գործոնների դասակարգմանը, ինչպես նաև ընտանիքի դիմակայության մոտեցմանը, որն ընտանիքի գործառնման նոր մոտեցում է առաջարկում։ В статье обсуждается феномен детей, лишённых опекунства с целью выявления базовых показателей функционирования семьи, значимых с точки зрения депривации детей. В частности, обсуждались подходы, предложенные Боулби, Спенсом, Кадушиным и Бернстайном, в контексте факторов риска, вызывающих отказ от детей. Кроме того, изучалась концепция устойчивости семьи как новый взгляд на функционирование семьи.
Keywords: Demography; Population; Vital Events